New Indications of Endothelial Dysfunction-Predictors of Recurrent Obstetric Bleeding - Karimova N. N.; Halimova E. M. (Central Asian Journal of Literature, Philosophy and Culture, 2022)
The main indicators of resume endothelial dysfunction are endothelin-1 (et-1), nitric oxide (no), E-selectin and vascular endothelial growth factor (VEGF). The current pregnancy clinical course was studied at 32 in 53anamnes of masiv kon in 32 of the departed fetters and at 32 of the healthy fetters in the control group, the endothelial dysfunction indicators hitandildai. In this regard, we decided to divide them into 2 groups: without the risk of falling, with the risk of falling. An individual analysis of the indicators of endothelial dysfunction showed a pronounced dysfunctional state in pregnant women of the group at risk of miscarriage. In 18-24 weeks of pregnancy, an increase in serum levels of pregnant women et-1 , no, Eselektin and VEGF in relation to the indicators of women with a physiological course of pregnancy was found to be 1.66; 1.2; 1.32 and 1.17 times. In pregnant women at risk of miscarriage, this excess was 3.33; 1.59; 1.72 and 1.68 times. It must be said that in this group of pregnant women, the level of et-1, no, E-selectin and VEGF is 2; 1.32; Pregnant women showed 1.31 and 1.44 times more values without the risk of miscarriage.